Preparation of autoclaved aerated concrete with mechanically or physically sound properties - Garg Arjun (2015)
Instead of pre-treating IBA to remove or to immobilize metallic aluminium, this paper proposes to utilize IBA as aerating agent to replace costly aluminium powder and as silica source to partially replace silica sand in the production of autoclaved aerated concrete (AAC). IBA-AACs with density ranging from 600 to 800 kg/m3 were successfully synthesized by using IBA as aerating agent. A detailed study was carried out to gain insight into the effects of varied dosage of IBA into AAC. Principle research points of the project include detailed study on the hydrogen gas generation to derive a relation between IBA and Al as aerating agent. Followed by marsh cone flow test to measure the trends in the yield stress of AAC with Al(70.4 μm) and IBA(45 μm) in varying proportions. Vicat needle test was performed to get the initial setting time of paste with and without the aerating agent. Lastly rising height of various samples with varying proportions was tested to measure the actual impact on the rising, which is one of the major considerations for aerated concrete as it affects the density of the final specimen. The control sample i.e using Al as aerating agent was casted and optimised first followed by IBA control sample i.e using IBA as the aerating agent. All the experiments allowed to come up with an optimised and effective mix procedure as well as mix design which was not available previously due to lack of standardisation for AAC. Also it was found that IBA could produce a maximum rising of 50% when pre-cured under a temperature of 80°C.